1996
DOI: 10.1038/ng1096-163
|View full text |Cite
|
Sign up to set email alerts
|

Imprint switching on human chromosome 15 may involve alternative transcripts of the SNRPN gene

Abstract: Imprinting on human chromosome 15 is regulated by an imprinting centre, which has been mapped to a 100-kb region including exon 1 of SNRPN. From this region we have identified novel transcripts, which represent alternative transcripts of the SNRPN gene. The novel exons lack protein coding potential and are expressed from the paternal chromosome only. We have also identified intragenic deletions and a point mutation in patients who have Angelman or Prader-Willi syndrome due to a parental imprint switch failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
177
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(188 citation statements)
references
References 33 publications
3
177
0
4
Order By: Relevance
“…On the other hand, 7 AS patients with an imprinting mutation had either a minute deletion or a base substitution at a region more proximal to SNRPN-exon 1. Novel alternative transcripts of S N R P N were identified from this region (Dittrich et al, 1996). Imprinting mutations do not disturb the whole imprinting phenomenon but may specifically involve only the P W S / A S region.…”
Section: [ As Lmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, 7 AS patients with an imprinting mutation had either a minute deletion or a base substitution at a region more proximal to SNRPN-exon 1. Novel alternative transcripts of S N R P N were identified from this region (Dittrich et al, 1996). Imprinting mutations do not disturb the whole imprinting phenomenon but may specifically involve only the P W S / A S region.…”
Section: [ As Lmentioning
confidence: 95%
“…The abnormality in these patients is referred to as an imprinting mutation. Detailed study demonstrated that three such PWS patients with imprinting mutations actually had a minute deletion involving exon 1 of S N R P N (Buiting et aL, 1994;Sutcliffe et al, 1994;Dittrich et al, 1996). On the other hand, 7 AS patients with an imprinting mutation had either a minute deletion or a base substitution at a region more proximal to SNRPN-exon 1.…”
Section: [ As Lmentioning
confidence: 96%
See 1 more Smart Citation
“…69,70 The SNRPN gene has a number of alternative transcripts, and AS-imprinting center overlaps with exons of such transcripts. 71,72 Therefore, one possible explanation for some cases would be that the deletions affect oocyte-specific alternative transcripts traversing the SNRPN ICR, and this results in a failure in imprint establishment. Prader-Willi syndrome (PWS) is another neurogenetic disorder that results from the abnormalities of the same imprinted cluster as AS.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…6 -8 Nearly all the cytosine phosphodiester guanine dinucleotides around the promoter region of the small nuclear ribonucleoprotein polypeptide N (SNRPN) gene are methylated on the maternal chromosome and completely devoid of methylation on the paternal chromosome. 9 The promoter methylation status of SNRPN is recognized as a valid diagnostic characteristic. 10 SNRPN, therefore, is a candidate gene for PWS and AS.…”
Section: Prader-willi Syndrome (Pws) [Omim (Online Mendelianmentioning
confidence: 99%